Phytoextraction of Metals from Contaminated Soil: A Review of Plant/Soil/Metal Interaction and Assessment of Pertinent Agronomic Issues - M. M. Lasat (Journal of Hazardous Substance Research, 1999)
Phytoremediation is an emerging technology that employs the use of higher plants for the cleanup of contaminated environments. Fundamental and applied research have unequivocally demonstrated that selected plant species possess the genetic potential to remove, degrade, metabolize, or immobilize a wide range of contaminants. Despite this tremendous potential, phytoremediation is yet to become a commercial technology. Progress in the field is precluded by limited knowledge of basic plant remedial mechanisms. In addition, the effect of agronomic practices on these mechanisms is poorly understood. Another limitation lies within the very biological nature of this novel approach. For example, potential for phytoremediation depends upon the interaction among soil, contaminants, microbes, and plants. This complex interaction, affected by a variety of factors, such as climatic conditions, soil properties, and site hydro-geology, argues against generalization, and in favor of site-specific phytoremediating practices. Thus, an understanding of the basic plant mechanisms and the effect of agronomic practices on plant/soil/contaminant interaction would allow practitioners to optimize phytoremediation by customizing the process to site-specific conditions. Remediation of metal-contaminated soil faces a particular challenge. Unlike organic contaminants, metals cannot be degraded. Commonly, decontamination of metal-contaminated soils requires the removal of toxic metals. Recently, phytoextraction, the use of plants to extract toxic metals from contaminated soils, has emerged as a cost-effective, environment-friendly cleanup alternative. In this paper, we review the processes and mechanisms that allow plants to remove metals from contaminated soils and discuss the effects of agronomic practices on these processes.
Keywords: phytoremediation; phytoextraction; toxic metals; metal hyperaccumulators